The (Lack of) Demand for Performance Information by the Croatian Parliament - Romea Manojlović Toman; Goranka Lalić Novak (Transylvanian Review of Administrative Sciences, 2019)
This paper explores the demand for performance information by members of the Croatian Parliament, and the supply thereof by the Croatian public administration. The research consists of data content analysis of parliamentary questions and answers in the first six months of 2015. The results show that the demand for performance information by MPs is lower than its supply by the administration. The MPs’ personal characteristics have an influence on the demand for performance information since higher demand is shown by those belonging to opposition parties, while those most experienced politically are the ones requesting least information. The influence of MPs’ education on the demand for performance information is not unequivocal. Two issues are further discussed: development of the performance management system and an increase in the power of executives, which can be a result of the Europeanization process.